Ryzyko, kryzys, trauma jako przedmiot oddziaływań reprezentantów profesji pomocowych – wybrane konteksty społeczne i psychologiczne - Bielska, Ewa; Czerkawski, Andrzej (Studia Edukacyjne, 2020)
The analysis covers chosen social (structural, systemic) and psychological determinants of the risk, crisis and trauma. Analysis emphasizes the factors essential from the perspective of activities realized by the representatives of social aid professions. It indicates the main risk factors of crisis and trauma, protective factors and chosen preventive and aid-related strategies realized in the crisis and trauma contexts (related to the different levels of their potential incidence).